A Model-Driven Approach for Wearable Systems Developments. (11th October 2015) - Ruiz-Zafra, Angel; Noguera, Manuel; Benghazi, Kawtar; Ochoa, Sergio F.
This paper proposes a model-driven approach for developing high-level software interfaces that allow developers to interact with wearable devices easily. These components hide the heterogeneity of the devices interfaces and provide developers with a simple and homogeneous way to interoperate with these digital peripherals. The use of this approach also allows reducing risks and development efforts.